The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/csc2.20630
|View full text |Cite
|
Sign up to set email alerts
|

Improving the foliar biofortification of broccoli with selenium without commercial quality losses

Abstract: Selenium‐biofortified broccoli (Brassica oleracea L. var. italica Plenck) is an important source of micronutrients in a healthy human diet. Therefore, studies are needed on the commercial production of selenium‐enriched broccoli. We analyzed the effect of the foliar application of sodium selenate and sodium selenite in doses of 50 and 100 g ha−1 on the growth, photosynthetic parameters, selenium accumulation, and commercial quality of broccoli in two cultivars (‘Belstar’ and ‘Legend’) used for fresh crops mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 52 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…It is known that broccoli harvest also affects head diameters with an increase due to florets opening, as part of the tissue decay and disorganization (Dixon, 2007). However, the diameter of broccoli heads was not significantly affected by Se foliar application at the harvest time; while the diameter ranges obtained were similar to previous reports (Ghasemi et al., 2016; Muñoz et al., 2021). Foliar application of Se salts, improved head diameter maintenance during postharvest, likewise the previous results.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…It is known that broccoli harvest also affects head diameters with an increase due to florets opening, as part of the tissue decay and disorganization (Dixon, 2007). However, the diameter of broccoli heads was not significantly affected by Se foliar application at the harvest time; while the diameter ranges obtained were similar to previous reports (Ghasemi et al., 2016; Muñoz et al., 2021). Foliar application of Se salts, improved head diameter maintenance during postharvest, likewise the previous results.…”
Section: Resultssupporting
confidence: 90%
“…In our previous work, we have reported that foliar application of Se salts at preharvest did not affect head firmness at harvest (Muñoz et al., 2021). In this work, a delay in the reduction of broccoli heads firmness, and even an augment in particular cases, during postharvest life, has been established.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations